2015
DOI: 10.1590/s0100-736x2015000700015
|View full text |Cite
|
Sign up to set email alerts
|

Ação trófica de aditivos fitogênicos, glutamina e ácido glutâmico sobre a Bursa de Fabrícius e intestino delgado de frangos de corte

Abstract: The aim of this study was to evaluate the effect of phytogenic additives and glutamine plus glutamic acid, associated or not, on histomorphometry of bursa of Fabricius and small intestine, oocyst count and lesion scores, and carbon turnover of duodenal mucosa of broiler chickens infected with Eimeria acervulina. A total of 450 male broiler chickens was distributed into a completely randomized design with six treatments and three replications. Treatments consisted of control diet (CD); CD + coccidiosis vaccine;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Histomorphometric studies of Bursa of Fabricius in birds subjected to stress conditions concluded that stress affects the development of bursa with increasing size; thus, the weight of lymphoid organs such as Bursa of Fabricius, for example, reflects the body's ability to produce lymphoid cells during the immune response [65].…”
Section: Discussionmentioning
confidence: 99%
“…Histomorphometric studies of Bursa of Fabricius in birds subjected to stress conditions concluded that stress affects the development of bursa with increasing size; thus, the weight of lymphoid organs such as Bursa of Fabricius, for example, reflects the body's ability to produce lymphoid cells during the immune response [65].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has been shown to reduce the damage caused by coccidiosis in chickens (Kim et al ., 2013;Pelícia et al ., 2015;Peek et al ., 2013). In our study, calves receiving 200 mg curcumin /animal/day had a reduction in oocyst excretion similar to that observed in lambs receiving oral doses of C .…”
Section: Discussionmentioning
confidence: 99%
“…the aromatic ring hydroxyls, the double bonds in the alkene, and the dike tone portion. These confer anti-inflammatory, antibacterial, antiviral, anticancer, antioxidant, and coccidiostatic activities (Almeida et al ., 2008;Pelícia et al ., 2015). Although it has known benefits in poultry, it is unclear as to whether curcumin may be useful in calves.…”
Section: Introductionmentioning
confidence: 99%